Coronary microvascular dysfunction equivalent to left main coronary artery disease - Cafer Panç; Mehmet Kocaağa; Onur Erdoğan; Remzi Sarıkaya; Sabahattin Umman (KARE Publishing, 2017)
Coronary microvascular dysfunction, also known as cardiac syndrome X, is a clinical syndrome presenting with typical angina and evidence of myocardial ischemia in the absence of ﬂow-limiting stenosis on coronary angiography. Of patients undergoing coronary angiography due to suspected myocardial ischemia, 50% are found to have normal or near-normal coronary arteries. Described in this case report is a patient who developed hypotension and ST segment depressions during treadmill exercise test. Left main coronary artery or multivessel disease was suspected. Coronary angiography was normal, but coronary flow reserve measurement revealed severe microvascular dysfunction.